Age-targeted chemotherapy for control of urinary schistosomiais in endemic populations - Charles H. King; Eric M. Muchiri; John H. Ouma (Memorias do Instituto Oswaldo Cruz, 1992)
Severity of urinary tract morbidity increases with intensity and duration of Schistosoma haematobium infection. We assessed the ability of yearly drug therapy to control infection intensity and reduce S. haematobium-associated disease in children 5-21 years old in an endemic area of Kenya. In year I, therapy resulted in reduced prevalence (66% to 22%, P < 0.001) and intensity of S. haematobium infection (20 to 2 eggs/10 mL, urine), with corresponding reductions in the prevalence of hematuria (52% to 19%, P < 0.001). There was not, however, a significant first-year effect on prevalence of urinary tract abnormalities detected by ultrasound. Repeat therapy in years 2 and 3 resulted in significant regression of hydronephrosis and bladder abnormalities (41% to 6% prevalence, P< 0.001), and further reductions in proteinuria. Repeat age-targeted therapy was associated with decreased prevalence of infection among young children (< 5yr) entering into the target age group. Two years after discontinuation of therapy, intensity of S. haematobium infection and ultrasound abnormalities remained suppressed, but hematuria prevalence began to increase (to 33% in 1989). Reinstitution of annual therapy in 1989 and 1990 reversed this trends. We conclude that annual oral therapy provides an effective strategy for control of morbidity due to S. haematobium on population basis, both through regression of disease in treated individuals, and prevention of infection in untreated subjects.